2007
DOI: 10.1515/cclm.2007.168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of analytic variations in creatinine measurements on the classification of renal disease using estimated glomerular filtration rate (eGFR)

Abstract: Small analytic changes in serum creatinine create major shifts in the distributions of eGFR, which can cause large differences in the classification of patients. The within-subject variations in eGFR over time, especially between hospital and clinic measurements, can be large. Therefore, tight control of laboratory analysis is important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…The presence of high glucose concentrations in plasma will result in either under or over estimation of GFR, according to the method used and may also lead to errors in classification of CKD. For example, in their study, Klee et al 14 reported that a positive bias of 20 mol/L in creatinine measurement, resulted in a three-fold increase the number of patients with GFR value of <60 mL/min/1.73 m 2 .…”
Section: Discussionmentioning
confidence: 97%
“…The presence of high glucose concentrations in plasma will result in either under or over estimation of GFR, according to the method used and may also lead to errors in classification of CKD. For example, in their study, Klee et al 14 reported that a positive bias of 20 mol/L in creatinine measurement, resulted in a three-fold increase the number of patients with GFR value of <60 mL/min/1.73 m 2 .…”
Section: Discussionmentioning
confidence: 97%
“…The impact of analytical performance characteristics of a creatinine method on eGFRcrea was demonstrated in the work by Klee et al 10 The same is true for cystatin C. Our study used creatinine and cystatin C tests traceable to international reference materials, which leads to low bias of both methods.…”
Section: T a B L E 1 Gfr Classification Stages According To Egfrs Andmentioning
confidence: 59%
“…In this study, the creatinine enzymatic IDMS-traceable assay used allowed to minimize the analytical bias on the study of agreement between the three methods than non-enzymatic creatinine determination [16].…”
Section: Discussionmentioning
confidence: 99%